Average Error: 0.0 → 0.0
Time: 7.9s
Precision: 64
$b \cdot b - \left(4 \cdot a\right) \cdot c$
$b \cdot b - \left(4 \cdot a\right) \cdot c$
b \cdot b - \left(4 \cdot a\right) \cdot c
b \cdot b - \left(4 \cdot a\right) \cdot c
double f(double b, double a, double c) {
double r19311881 = b;
double r19311882 = r19311881 * r19311881;
double r19311883 = 4.0;
double r19311884 = a;
double r19311885 = r19311883 * r19311884;
double r19311886 = c;
double r19311887 = r19311885 * r19311886;
double r19311888 = r19311882 - r19311887;
return r19311888;
}


double f(double b, double a, double c) {
double r19311889 = b;
double r19311890 = r19311889 * r19311889;
double r19311891 = 4.0;
double r19311892 = a;
double r19311893 = r19311891 * r19311892;
double r19311894 = c;
double r19311895 = r19311893 * r19311894;
double r19311896 = r19311890 - r19311895;
return r19311896;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$b \cdot b - \left(4 \cdot a\right) \cdot c$
2. Final simplification0.0

$\leadsto b \cdot b - \left(4 \cdot a\right) \cdot c$

# Reproduce

herbie shell --seed 1
(FPCore (b a c)
:name "b*b-4*a*c"
(- (* b b) (* (* 4.0 a) c)))